Potential antimicrobial coconut oil in the treatment of wounds - Almeida, Lícia Caroline Tenório de; Tenório, Lis Maria de Melo Carvalho; Verissímo, Regina Célia Sales Santos; Lúcio, Ingrid Martins Leite; Bastos, Maria Lysete de Assis (Rev Rene, 2012)
New means of controlling infection in wounds appear on the public health implications in the care, development of technologies and products related to healing and controlling of microorganisms. Technological innovation in wound care is guided in plants with antimicrobial properties and healing with ethno botanist reports. Experimental in vitro study developed in the Research Laboratory of Wound Care between March and September 2011 that investigated the antimicrobial potential of the extract of coconut oil in view of infection prevention and treatment of wounds, using three extracts of coconut Alagoas (two craft and one industrialized) against 14 microorganisms to verify the antimicrobial activity, all of those extracts showed activity against Staphylococcus aureus, however for Staphylococcus epidermidisand Enterobacter cloacae, only artisanal oils worked. Tests for the extracts for purification and identification of the inhibitory substances of microorganisms as well as in vivo studies in wounds using animal model were needed.